Effect of Periodontal Therapy on Crevicular Fluid Interleukin-6 and Interleukin-8 Levels in Chronic Periodontitis - Paschalina Goutoudi; Evdoxia Diza; Malamatenia Arvanitidou (Hindawi Limited, 2012)
Purpose. The aim of this study was to analyse the levels of interleukin-6 (IL-6) and interleukin-8 (IL-8) in gingival crevicular fluid (GCF) of patients with chronic periodontitis prior to and following surgical and/or nonsurgical periodontal therapy for a period of 32 weeks. Methods. GCF samples were obtained from 24 nondiseased and 72 diseased sites of 12 periodontal patients prior to as well as at 6, 16, and 32 weeks following non-surgical and surgical periodontal therapy. IL-6 and IL-8 levels were determined by enzyme-linked immunosorbent assay (ELISA). Results. Periodontal treatment improved all clinical parameters. Both treatment modalities resulted in similar IL-6 as well as IL-8 levels. Mean IL-6 and IL-8 concentrations were significantly higher in non-diseased compared to diseased sites and increased significantly following treatment in diseased sites. Mean total amounts of IL-6 and IL-8 (TAIL-6, TAIL-8) did not differ significantly between diseased and nondiseased sites, while following therapy TAIL-8 levels decreased significantly. Conclusions. The data suggest that periodontal therapy reduced the levels of IL-8 in GCF. However, a strong relationship between IL-6, IL-8 amounts in GCF and periodontal destruction and inflammation was not found.